THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY AND RISK PROBABILITY TO THE REVENUE OF FOOD AND BEVERAGE COMPANIES LISTED IN INDONESIA STOCK EXCHANGE 2013-2018 PERIOD - Sunaryo, Deni (Dinasti Publisher, 2020)
A This study aims to determine the effect of Corporate Social Responsibility and risk probability on income in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2013-2018. The independent variable used in this study is Corporate Social Responsibility and risk probability. The dependent variable used is income. The sampling method used in this study used a purposive sampling technique and obtained 7 companies. The data collected is secondary data with the method of documentation through www.idx.com in the form of a company annual report. The analytical tool used for hypothesis testing is SPPS 23. The results of the study show that Corporate Social Responsibility has no significant effect on corporate earnings. Whereas, the probability of risk has a significant effect on company earnings. Then the Corporate Social Responsibility and risk probability together (simultaneous) have a significant influence on company income.bstract written in one paragraph using standard with enhanced spelling. 150 words maximum, using Times New Roman font size 12, space 1, Italic. Contains a brief overview of the overall results of the study including the background of the problem, objectives, methods, results, and conclusions. Avoid writing citations and abbreviations in abstracts.